Rodrigo Guijarro Lasheras. Punto contra punto: Una teoría de la música en la literatura. Madrid: Iberoamericana, 2023, 298 págs.: Review (Castilla. Estudios de Literatura, 2025)
The text is a review of the work Punto contra punto: una teoría de la música en la literatura, written by Rodrigo Guijarro Lasheras, edited in Madrid by Iberoamericana / Vervuert and published in 2023. The paper explains what issues does the author address in each part of the book, as well as it emphasises the relevance of its content and the contribution it represents to the academic and intellectual world. Some aspects related to Literary Theory and the situation of Musical-literary Studies, which work as the axis of the treatise, are also mentioned; taking into account the Guijarro Lasheras' opinions.
Keywords: Musical Literature; Music and Literature; Literary Theory; Musical novel